Hegemoni Gaya Hidup Dan Musik Slank Dalam Membangun Loyalitas “Slankers” - Shafira, Dara; Bandiyah, Bandiyah; Ali Azhar, Muhammad (Jurnal Nawala Politika, 2019)
ABSTRACT Slank is a band or musician who has a huge influence on his fans in Indonesia. Not many bands have as much fan base as Slank. The research entitled